Nocturnal migratory songbirds adjust their travelling direction aloft: evidence from a radiotelemetry and radar study - Sjöberg, Sissel (Biol Lett, 2015)
In order to fully understand the orientation behaviour of migrating birds, it is important to understand when birds set their travel direction. Departure directions of migratory passerines leaving stopover sites are often assumed to reflect the birds' intended travel directions, but this assumption has not been critically tested. We used data from an automated radiotelemetry system and a tracking radar at Falsterbo peninsula, Sweden, to compare the initial orientation of departing songbirds (recorded by radiotelemetry) with the orientation of songbird migrants in climbing and level flight (recorded by radar). We found that the track directions of birds at high altitudes and in level flight were more concentrated than the directions of departing birds and birds in climbing flight, which indicates that the birds adjust their travelling direction once aloft. This was further supported by a wide scatter of vanishing bearings in a subsample of radio-tracked birds that later passed an offshore radio receiver station 50 km southeast of Falsterbo. Track directions seemed to be more affected by winds in climbing compared with level flights, which may be explained by birds not starting to partially compensate for wind drift until they have reached cruising altitudes.